Uji Efektivitas Antioksidan Serum Ekstrak Daun Randu (Ceiba Pentandra (L.) Gaertn.) Dengan Metode DPPH - Muadifah, Afidatul; Ummah, Ratih Salimil; Tilarso, Dara Pranidya (Jurnal Farmasi & Sains Indonesia, 2023)
The development of cosmetics from natural ingredients has been widely applied in several cosmetic industries, one of the developing cosmetic dosage forms is serum. One of the plants that can be used for serum is randu leaf (Ceiba pentandra (L.) Gaertn.) which contains secondary metabolites including flavonoids, alkaloids, saponins, and tannins which act as natural antioxidants for antiaging. This study aims to determine the optimum levels of flavonoids in randu leaf extract using a UV-Vis spectrophotometer, physical quality of preparations and antioxidant activity in serum preparations using the DPPH method. In determining the levels of flavonoids in the randu leaf extract with concentration series of 20 ppm, 40 ppm, 60 ppm using a UV-Vis spectrophotometer, the results obtained were the optimum concentration of cotton leaf extract in the 60 ppm concentration series, which was 229.3 µg/ml. Then the serum preparation was made, it was found that the serum preparations of randu leaf extract and vitamin C had fulfilled the physical quality test requirements. The antioxidant activity test of serum preparations was continued using the DPPH method using a UV-Vis spectrophotometer and ascorbic acid as a comparison. The ????????50 value for the randu leaf extract serum preparation was 75.0159 ppm which was classified as having strong antioxidant activity while the vitamin C serum preparation was 4.674 ppm which was classified as having very strong antioxidant activity